PENGEMBANGAN RPM MENULIS TEKS ANEKDOT BENTUK KOMIK DENGAN CANVA SISWA KELAS X - Wijayanti, Minuk; Sujinah; Suher (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by students' low ability to write anecdotal texts, particularly in developing creative, critical, and contextual ideas related to social phenomena. Furthermore, learning remains conventional. Therefore, learning tools are needed that support meaningful, conscious, and enjoyable learning, in accordance with the characteristics of vocational high school students. This study aims to describe the development, practicality, and effectiveness of an In-Depth Learning Plan (RPM) for writing anecdotal texts in comic form using Canva. This study used the Borg and Gall Research and Development (R&D) model, modified into seven stages: needs analysis, planning, design, validation, revision, trial, and final product. The study subjects consisted of 35 grade 10 students of the KKB SMK Teknik Pal Surabaya in the 2025/2026 academic year, an Indonesian language teacher as the user of the RPM product, and a validator who was a material/learning expert. Data were collected through interviews, observations, questionnaires, documentation, and learning outcome tests, which were analyzed descriptively using qualitative and quantitative methods. The results showed that the developed RPM met the criteria of validity, practicality, and effectiveness. Validation by material/learning experts resulted in a score of 85% and validation by teacher users at 84%, categorized as very feasible. The practicality of the RPM, based on teacher responses, reached 98% (very practical), while student responses indicated that 25 students (65.71%) stated it was very practical and 12 students (34.29%) stated it was practical. The effectiveness of the RPM, based on student learning completion, was 97.14% with an average score of 82.77, and the anecdotal comic product was categorized as good to very good. Therefore, the RPM, which uses Canva to write anecdotal comics, is suitable for use in Indonesian language learning for 10th grade vocational high schools.